2009
DOI: 10.3748/wjg.15.1289
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of liver cancer

Abstract: Improvements in imaging technology allow exploitation of the dual blood supply of the liver to aid in the identification and characterisation of both malignant and benign liver lesions. Imaging techniques available include contrast enhanced ultrasound, computed tomography and magnetic resonance imaging. This review discusses the application of several imaging techniques in the diagnosis and staging of both hepatocellular carcinoma and cholangiocarcinoma and outlines certain characteristics of benign liver lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 97 publications
3
60
0
4
Order By: Relevance
“…Therefore HCC surveillance has been recommended by expert associations to improve survival of patients by identifying tumors in earlier stages [2][3][4] . Conventional or baseline ultrasound (BUS) is often used as the first-line tool for HCC surveillance, as well as for the detection of HCC or other focal liver lesions (FLLs) because of its efficiency, availability, non-invasiveness, and relatively low cost [5] . However, in view of the low ability of BUS to demonstrate tumor vascularity, it is sometimes difficult to differentiate benign FLLs (generally having a preferential portal venous blood supply) from malignant ones (generally having a preferential hepatic arterial supply) using BUS alone [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore HCC surveillance has been recommended by expert associations to improve survival of patients by identifying tumors in earlier stages [2][3][4] . Conventional or baseline ultrasound (BUS) is often used as the first-line tool for HCC surveillance, as well as for the detection of HCC or other focal liver lesions (FLLs) because of its efficiency, availability, non-invasiveness, and relatively low cost [5] . However, in view of the low ability of BUS to demonstrate tumor vascularity, it is sometimes difficult to differentiate benign FLLs (generally having a preferential portal venous blood supply) from malignant ones (generally having a preferential hepatic arterial supply) using BUS alone [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Although CT is the most commonly used imaging modality in HCC, it remains relatively insensitive for the detection of small HCC or intrahepatic metastases, especially in cirrhotic patients [6]. MRI provides higher lesion to liver contrast than CT, and …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the treatment response and survival of hepatocellular carcinoma (HCC) patients are related to the delivered radiation dose [1][2][3]. Recently, detailed information on HCC and liver motion gained from the use of advanced techniques, such as a fiducial marker combined with fourdimensional (4D) planning CT, has enabled the delivery of higher doses of radiation therapy (RT) with reduced normal liver toxicity [3][4][5].Although triphasic CT can provide much information about HCC, the lesion/liver contrast is higher in MRI than in CT [6,7]. To take advantage of these benefits, there have been many efforts to incorporate liver MRI in the RT planning process [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic diseases account for the majority of malignant lesions in the liver and up to 25 % of patients with known solid malignant tumors have hepatic metastases at the time of diagnosis [22]. Liver metastases can originate from numerous primary cancers (colorectal, mammary, lung, pancreatic, gastric, esophageal, melanoma and sarcoma among others).…”
Section: Fdg In Liver Metastases From Other Malignanciesmentioning
confidence: 99%